Mechanical Properties of Nanofilled Polypropylene Composites - Cristina-Elisabeta PELIN; Adriana STEFAN; George PELIN; Ion DINCA; Anton FICAI; Ecaterina ANDRONESCU; Georgeta VOICU (INCAS Bulletin, 2015)
The paper presents a study concerning mechanical performance of thermoplastic nanocomposites based on isotactic polypropylene matrix, nanofilled with montmorillonite modified with quaternary ammonium salt and carboxyl functionalized carbon nanotubes, respectively, added in the same concentration relative to the matrix. The nanofilled and single polymer materials were obtained by simple melt compounding through extrusion process followed by injection molding into specific shape specimens for mechanical testing of the samples. Mechanical properties were evaluated by tensile and 3 point bending tests. In terms of modulus of elasticity, the results showed overall positive effects concerning the effect of nanofiller addition to the thermoplastic polymer. The fracture cross section of the tested specimens was characterized by FT-IR spectroscopy and SEM microscopy.